2010
DOI: 10.2215/cjn.08261109
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Fluoroquinolones for the Prevention of BK Viremia after Renal Transplantation

Abstract: Background and objectives: Nearly 30% of renal transplant recipients develops BK viremia, a prerequisite for BK nephropathy. Case reports have evaluated treatment options for BK virus, but no controlled studies have assessed prophylactic therapies. Fluoroquinolone antibiotics were studied for prevention of BK viremia after renal transplantation.Design, setting, participants, & measurements: This retrospective analysis evaluated adult renal transplant recipients with at least one BK viral load (blood) between 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 26 publications
(42 reference statements)
3
84
0
Order By: Relevance
“…Quinolones have in vitro as well as in vivo effects on the BK virus. Observational studies have shown a reduction in the incidence of BK nephropathy with 1 month of ciprofloxacin therapy, and the "antiviral" effect seemed to persist even a year after the completion of treatment, suggesting that it can be used for the primary prevention of BK viral infection [27]. The clinical use of intravenous immunoglobulin has been limited owing to lack of clear benefit [28].…”
Section: Treatmentmentioning
confidence: 99%
“…Quinolones have in vitro as well as in vivo effects on the BK virus. Observational studies have shown a reduction in the incidence of BK nephropathy with 1 month of ciprofloxacin therapy, and the "antiviral" effect seemed to persist even a year after the completion of treatment, suggesting that it can be used for the primary prevention of BK viral infection [27]. The clinical use of intravenous immunoglobulin has been limited owing to lack of clear benefit [28].…”
Section: Treatmentmentioning
confidence: 99%
“…In kidney transplant recipients, a 10-day course of gatifloxacin was shown to decrease BK viremia in 7 of 10 patients after 2 months of follow-up. The effective use of fluoroquinolones as prophylaxis against the development of BK viremia has also been studied in both the hematopoietic stem cell transplant and kidney transplant populations (14,16,17). Gabardi et al showed that a 1-month course of fluoroquinolones after kidney transplantation was associated with significantly lower rates of BK viremia at 1 year (14).…”
Section: Discussionmentioning
confidence: 99%
“…Duration of therapy was based on our previous study on the use of levofloxacin in the prevention of BK viremia (14).…”
Section: Trial Design and Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of leflunomide, cidofovir, IVIg and fluoquinolones as adjunct therapy in addition to immunosuppression reduction in the management of BK virus nephropathy has been evaluated in several small clinical studies [3][4][5][6]. There have however been no prospective randomized studies to compare the various agents and provide much needed information on long-term benefits.…”
Section: Introductionmentioning
confidence: 99%